1992ネン ～ 1994ネン ノ ナンキョク タイリク エンガン テイチャク ヒョウイキ ニ オケル チンコウ リュウシ フラックス ノ ヘンドウ - 鈴木, 英勝; スズキ, ヒデカツ; 佐々木, 洋; ササキ, ヒロシ; 谷村, 篤; タニムラ, アツシ; 福地, 光男; フクチ, ミツオ; SUZUKI, Hidekatsu; SASAKI, Hiroshi; TANIMURA, Atsushi; FUKUCHI, Mitsuo (1998)
P(論文) 1992年の1月から1994年の1月までの間, 南極昭和基地周辺の定着氷域の8観測点において, 沈降粒子フラックスの変動を観測するためにセディメントトラップ吊下実験を行った。表層付近(≦約50m)のフラックスは顕著な季節変化を示し, 0 (<0.1) mgDW m^<-2> d^<-1>(1993年冬季)から2765mgDW m^<-2> d^<-1>(1993-1994年夏季)の間で変動した。夏季にはフラックスは高く, 冬季には低く, 中間期(春季及び秋季)においては不規則な変動が見られた。深層(>約50m)のフラックスに季節変化は観察されなかった。50m以浅のフラックスから周年変化を概観すると, 1992年(25gDW m^<-2> y^<-1>)と1993年(159gDW m^<-2> y^<-1>)では明らかに1993年において年間積算乾燥重量フラックスが高いと見積もられた。また複数測点間のフラックスの変動及び, 遊泳性動物プランクトンの混入による正味のフラックスに対する過大評価(最大167%)も認められ, これらがフラックス推定の誤差を生じさせる原因となる可能性を示した。 Sediment trap experiments were done to investigate variability flux of sinking particles from eight stations under fast ice near Syowa Station, Antarctica, from January 1992 to January 1994. The fluxes in the shallow water column (≦ca. 50m) showed marked seasonality ranging from 0 (<0.1) mgDW m^<-2> d^<-1> in winter 1993 to 2765 mgDW m^<-2> d^<-1> in summer 1993-1994. They were high in summer, low in winter and variable in the transitional season (spring and fall). The flux in the deep water column (>ca. 50m) not showed marked seasonality. The annual flux in 1993 (159gDW m^<-2> y^<-1>) was larger than that in 1992 (25gDW m^<-2> y^<-1>) in ≦ca. 50m. A marked variation in the flux among sampling stations was found during summer in 1992. The flux of zooplankton swimmers, which changed with season and depth, greatly contributed to the net flux (maximum 167%) under fast ice. departmental bulletin paper